Analysis of The Influence of Additional Percentage of Catalyst on The Electrolysis Process on Hydrogen Volume and Flame Profile - Mohammad Julio Akbar; Gatot Soebiyakto; Akhmad Farid; Dadang Hermawan (Widyagama University of Malang, 2023)
Utilization of new and renewable energy is an important point for Indonesia for development, science and technology. On the other hand, the use of fossil fuels is very limited so the alternative fuel solutions are vegetable oil (BBN) and methane gas and others, even in the future the substitute for these fuels will use electricity. The material used in this research is stainless steel. The independent variable tested was the catalyst percentage of NaCl, NaOH and NaHCO3 of 40%. The dependent variables are the volume of hydrogen and flame characteristics. The control variable uses a voltage of 12 volts using water and distilled water as solvents with a volume of 1000 ml. The data collection procedure starts with 12 Volt DC current energy which will produce electrical energy from the cathode pole and anode pole. The electrolysis process will occur causing the catalyst and solution to undergo a chemical process, namely the separation/decomposition of H2O, the catalyst and solution producing hydrogen bubbles which are stored in a tube. The data is then analyzed empirically and using Image-J software or similar to determine the characteristics of the flame. The analysis of the experimental data above can be compared with previous research, namely producing the highest volume of hydrogen at a percentage of 16% of 367 mL and the lowest volume of hydrogen at a percentage of 8% of 198 mL. The highest flame temperature at a percentage of 16% is 54.7 C and the lowest temperature at a percentage of 8% is 31.7C with the highest flame height at a percentage of 16% being 5.72cm and a flame width of 2.98cm and the flame brightness level (Red Green Blue) is highest at a catalyst percentage of 16% at 16 RGB and the flame brightness level (Red Green Blue) is lowest at a percentage of 8% at 2 RGB.